Investigation of the effect of graphene oxide nanoparticles on the structural and dielectric parameters in zinc oxide semiconductors - Horlu, Merve; Macit, Cevher Kursat; Aksakal, Bunyamin; Tanyeri, Burak; Biryan, Fatih (Springer, 2024)
In this study, pure and 1%, 3% and 5% doped graphene oxide (GO) reinforced zinc oxide (ZnO) nanoparticles were synthesized by sol-gel method. The aim was to improve the electrical and dielectric properties of ZnO semiconductor metal oxide used in many electronic, optoelectronic and electrochemical technologies. FE-SEM, X-ray diffraction (XRD), Raman spectroscopy, energy dispersive spectroscopy and Fourier transform infrared spectroscopy (FT-IR), were used to show the structural and morphological properties of the synthesized ZnO and GO doped ZnO nanoparticles. Impedance analysis was used to study the dielectric properties of the produced nanoparticles. XRD analysis revealed typical peaks of nGO and ZnO nanoparticles. Through the FE-SEM and XRD analysis, it was shown that the ZnO and GO nanopowders were successfully synthesized. The results revealed that ZnO-GO nanoparticles, having good dielectric constant with loss and AC conductivity values, such materials can be a good candidate for solar cells and photovoltaic devices. GO reinforced ZnO nanoparticles with high purity and homogeneity were produced by sol-gel synthesis.Structural and morphological analyses revealed that GO nanoparticles were incorporated into ZnO nanoparticles and retained their characteristic peaks.According to FE-SEM images, ZnO nanoparticles and GO nanoparticles were homogeneously dispersed on the surface of ZnO nanorods and plates. The crystal diameters, unit cell volume and lattice properties of the nanoparticles increased with increasing GO addition.The addition of GO to ZnO nanoparticles improved their dielectric response and the addition of GO to the electrical conductivity had a positive effect on ZnO nanoparticles.
Keywords: Nanomaterial; Sol-gel; Semiconductor; Graphene oxide doped zinc oxide; Conductivity